Uji Aktivitas Antibakteri Ekstrak Etanol Daun Gaharu (Aquilaria malaccensis) Dengan Menggunakan Metode KLT-Bioautografi - Amri, Andhika Ulil (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
The gaharu plant (Aquilaria malaccensis) has antibacterial properties. The chemical compounds contained in gaharu leaves are flavonoids, alkaloids, and tannins. This study aims to determine the antibacterial activity of the ethanol extract of gaharu (Aquilaria malaccensis) leaves. In this study, gaharu leaf simplicia was extracted using the maceration method with 96% ethanol solvent, after which a liquid extract was obtained and then evaporated using a rotary evaporator to obtain a thick extract. After obtaining the thick extract, a screening test was carried out with concentrations of 0.1 and 0.5% against 3 test bacteria namely Staphylococcus aureus, Pseudomonas aeruginosa, Propionibacterium acnes. Then proceed with TLC-Bioautography testing using chloroform: methanol (1: 4) eluent and then proceed with the identification of the components of the chemical compound. The results of the screening test showed that the ethanol extract of gaharu leaves (Aquilaria malaccensis) showed activity against 3 test bacteria at a concentration of 0.5%. The results of the TLC-Bioautography test showed that there was 1 spot produced with an Rf value of 0.65 against the bacteria Staphylococcus aureus, Pseudomonas aeruginosa, Propionibacterium acnes. The results of identification of the chemical components of the ethanol extract of gaharu leaves (Aquilaria malaccensis) gave positive results containing flavonoids, alkaloids, and tannins. Based on the activity of the ethanol extract of gaharu leaves (Aquilaria malaccensis) it has potential as an antibacterial.